Temporal differentiation of bovine airway epithelial cells grown at an air-liquid interface. Issue 1 (December 2018) - Cozens, Daniel; Sutherland, Erin; Marchesi, Francesco; Taylor, Geraldine; Berry, Catherine; Davies, Robert
Abstract There is an urgent need to develop improved, physiologically-relevantin vitro models of airway epithelia with which to better understand the pathological processes associated with infection, allergies and toxicological insults of the respiratory tract of both humans and domesticated animals. In the present study, we have characterised the proliferation and differentiation of primary bovine bronchial epithelial cells (BBECs) grown at an air-liquid interface (ALI) at three-day intervals over a period of 42 days from the introduction of the ALI. The differentiated BBEC model was highly representative of theex vivo epithelium from which the epithelial cells were derived; a columnar, pseudostratified epithelium that was highly reflective of native airway epithelium was formed which comprised ciliated, goblet and basal cells. The hallmark defences of the respiratory tract, namely barrier function and mucociliary clearance, were present, thus demonstrating that the model is an excellent mimic of bovine respiratory epithelium. The epithelium was fully differentiated by day 21 post-ALI and, crucially, remained healthy and stable for a further 21 days. Thus, the differentiated BBEC model has a three-week window which will allow wide-ranging and long-term experiments to be performed in the fields of infection, toxicology or general airway physiology.